2013
DOI: 10.1098/rsbl.2013.0163
|View full text |Cite
|
Sign up to set email alerts
|

A novel hearing specialization in the New Zealand bigeye,Pempheris adspersa

Abstract: The New Zealand bigeye, Pempheris adspersa, is a nocturnal planktivore and has recently been found to be an active sound producer. The rostral end of the swim bladder lies adjacent to Baudelot's ligament which spans between the bulla and the cleithrum bone of the pectoral girdle. The aim of this study was to use the auditory evoked potential technique to physiologically test the possibility that this structure provides an enhanced sensitivity to sound pressure in the bigeye. At 100 Hz, bigeye had hearing sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The temporal and spectral characteristics of the bigeye sound differed from the vocalisation of another congeneric species, the silver sweeper P. schwenkii, found in tropical waters (Takayama et al, 2003). The silver sweeper produces a single sound type consisting of two to seven pulses with an average duration of 56 ms from the contraction of paired extrinsic sonic muscles that are attached to a doublechambered swim bladder, which is similar to the bigeye (Radford et al, 2013). Silver sweeper vocalisations cover a narrower frequency band-width (200 Hz) with three harmonically related frequency peaks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The temporal and spectral characteristics of the bigeye sound differed from the vocalisation of another congeneric species, the silver sweeper P. schwenkii, found in tropical waters (Takayama et al, 2003). The silver sweeper produces a single sound type consisting of two to seven pulses with an average duration of 56 ms from the contraction of paired extrinsic sonic muscles that are attached to a doublechambered swim bladder, which is similar to the bigeye (Radford et al, 2013). Silver sweeper vocalisations cover a narrower frequency band-width (200 Hz) with three harmonically related frequency peaks.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid decay of the pulsed sound and low Q (0.82±0.02) indicated that the bigeye has a highly damped sound production mechanism typical of an extrinsic swim bladder muscle-generated sound (Fine et al, 2001(Fine et al, , 2009Radford et al, 2013). A high level of damping allows efficient temporal patterning of the pulses (Fine et al, 2004;Lindström and Lugli, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inner ear is also sensitive to the particle movement of an acoustic fi eld as a result of whole-body accelerations (Rogers and Cox 1988 ;Montgomery et al 2006 ), through the differential movement of the denser otolith with the body motions of the fi sh. Sound pressure can be detected by fi sh from pressure-induced oscillations of the walls of an air pocket, such as the swim bladder, that then are transduced into mechanical stimuli appropriate to sensors (Higgs et al 2006), such as the hair cells of the inner ear (Montgomery et al 2006 ) or possibly the hair cells of the neuromasts that overlie laterophysic or otolaterophysic connections (Webb 1998 ;Webb and Smith 2000 ;Radford et al 2013 ). The inner ear often lies just medial to the confl uence of several cephalic lateral line canals (Fig.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…Kenyon 1996 ;Higgs et al 2002Higgs et al , 2003Caiger et al 2013 ), how experimental manipulations can affect detection (e.g. Yan et al 2000 ;Radford et al 2012Radford et al , 2013Higgs and Radford 2013 ), and to examine the bandwidth of detection between different species of interest (e.g. Corwin et al 1982;Kenyon et al 1998 ;Niemiller et al 2013 ).…”
Section: "Hearing" As a Physiological Responsementioning
confidence: 99%